Does pension privatization increase economic growth? Evidence from Latin America and Eastern Europe*. (3rd October 2016) - ALTIPARMAKOV, NIKOLA; NEDELJKOVIĆ, MILAN
Abstract: Analyses of pension funding effects on economic growth should differentiate between 'carve-out' pension privatization in Latin America and Eastern Europe and typical 'add-on' pension funding in Western Europe and North America. We find no evidence that pension privatization in Latin America and Eastern Europe was associated with higher economic growth. The result is robust across both continents and several alternative econometric specifications. Positive growth effects are particularly unlikely in countries resorting to debt-financed privatization. Furthermore, we note the lack of positive pension privatization effects on savings in Eastern Europe, with limited evidence of positive savings effects in Latin America. These findings suggest that cost-containment parametric reforms should be given priority over carve-out pension privatization when considering options for restoring financial sustainability of public Pay-As-You-Go systems.